ANALISIS KLASTER MULTIDIMENSI PADA PERIKANAN SKALA KECIL TUNA DAN CAKALANG DI MALUKU TENGAH - Welem Waileruny; Stany Rachel Siahainenia; Taufiriningsih Kesaulya (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
This study examines the multidimensional performance of small-scale tuna and skipjack fisheries across four major locations in Central Maluku—Banda, Saparua, Amahai, and Tehoru—using five key dimensions: social, economic, technological, institutional, and ecological. Cluster analysis was applied to classify locations based on their multidimensional characteristics and to identify the dimensions most influential in shaping cluster separation. The findings reveal distinct differences among sites, with Saparua exhibiting the strongest social and institutional performance, Banda showing the weakest institutional conditions, and Amahai–Tehoru forming a single cluster characterized by relatively strong economic and technological conditions but weaker ecological performance, particularly in Tehoru. Institutional and social dimensions emerged as the primary drivers of cluster formation, followed by technological, economic, and ecological factors. The discussion highlights how institutional strength and social capital underpin adaptive capacity and economic–ecological outcomes, while technological intensification may heighten exploitation risks without effective effort regulation. The study concludes that fisheries management must be tailored to cluster-specific contexts: strengthening local institutions in Banda, consolidating co-management in Saparua and Amahai, and implementing effort controls and ecological monitoring in Tehoru. These results reinforce the importance of place-based and socially rooted governance in small-scale fisheries.